2017
DOI: 10.1117/1.jbo.22.2.025001
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying cerebral hypoxia by near-infrared spectroscopy tissue oximetry: the role of arterial-to-venous blood volume ratio

Abstract: "Quantifying cerebral hypoxia by near-infrared spectroscopy tissue oximetry: the role of arterial-tovenous blood volume ratio," J. Biomed. Opt. 22(2), 025001 (2017), doi: 10.1117/1.JBO.22.2.025001. Abstract. Tissue oxygenation estimated by near-infrared spectroscopy (NIRS) is a volume-weighted mean of the arterial and venous hemoglobin oxygenation. In vivo validation assumes a fixed arterial-tovenous volume-ratio (AV-ratio). Regulatory cerebro-vascular mechanisms may change the AV-ratio. We used hypotension to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
3
6
0
Order By: Relevance
“…During hypoxia, the decline of rcSO 2 reflects a concurrent decrease in arterial oxy-haemoglobin saturation and a rise in venous deoxy-hemoglobin saturation (10). In addition, Rasmussen et al (19) indicated that cerebral NIRS oximetry responded poorly to changes in tissue oxygenation during hypotension that was induced by decreased preloading. This may be due to the increase in the artery-to-vein ratio that occurs following the decrease in oxygen delivery, which is due to arterial vasodilation and possibly cerebral venous collapse.…”
Section: Discussionmentioning
confidence: 99%
“…During hypoxia, the decline of rcSO 2 reflects a concurrent decrease in arterial oxy-haemoglobin saturation and a rise in venous deoxy-hemoglobin saturation (10). In addition, Rasmussen et al (19) indicated that cerebral NIRS oximetry responded poorly to changes in tissue oxygenation during hypotension that was induced by decreased preloading. This may be due to the increase in the artery-to-vein ratio that occurs following the decrease in oxygen delivery, which is due to arterial vasodilation and possibly cerebral venous collapse.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio differs according to the device, and the assumed ratio is 25:75 for the INVOS ® and 30:70 for the FORE-SIGHT ® , EQUANOX ® , and NIRO ® [17]. A previous study showed that blood pressure could affect cerebral oximetry values according to the A/V ratio [18]. O3 TM can change its preset A/V ratio between 25:75 and 30:70; therefore, it would be a useful device with an adjustable setting based on the clinical situation or blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…If FIRS resulted in a centralization of the circulation, this may have changed the ratio of the arterial, capillary and venous compartments. As a consequence this resulted in a local decrease of oxygen consumption, because of a higher proportion of arterial blood vessels (relative to reduced number of capillary vessels within the measurement compartments), resulting in higher values of crSO2 and consecutively in lower cFTOE values ( 27 , 28 ). However, we do not have detailed information about the behavior of cerebral blood flow to define exact changes in cerebral perfusion to prove the underlying mechanism of the observed differences between groups ( 13 , 14 , 29 ).…”
Section: Discussionmentioning
confidence: 99%